2021
DOI: 10.1002/hep.31749
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Ameliorates Nonalcoholic Steatohepatitis by Activation of the AMP‐Activated Protein Kinase Signaling Pathway

Abstract: BaCKgRoUND aND aIMS: Nonalcoholic fatty liver disease, especially nonalcoholic steatohepatitis (NASH), has become a major cause of liver transplantation and liverassociated death. NASH is the hepatic manifestation of metabolic syndrome and is characterized by hepatic steatosis, inflammation, hepatocellular injury, and different degrees of fibrosis. However, there is no US Food and Drug Administration-approved medication to treat this devastating disease. Therapeutic activators of the AMP-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…AMPK is a key regulator that controls energy homeostasis. Previous studies have indicated that AMPK activation could prevent the progress of NASH (Hu et al, 2021;Lan et al, 2021). Our data have shown that PEA significantly enhanced AMPK phosphorylation, suggesting that AMPK may be the center regulator of lipid metabolism in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…AMPK is a key regulator that controls energy homeostasis. Previous studies have indicated that AMPK activation could prevent the progress of NASH (Hu et al, 2021;Lan et al, 2021). Our data have shown that PEA significantly enhanced AMPK phosphorylation, suggesting that AMPK may be the center regulator of lipid metabolism in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Hepatic lipid metabolism is crucial for the controlling of the lipid homeostasis in whole body. Lipid metabolism is a complex process involved in the regulation of some crucial nuclear factors, such as fatty acid-binding proteins (FABPs), peroxisome proliferator-activated receptor γ (PPARγ ), CD36, and SCD1 (7). FABPs modulate lipid fluxes, trafficking, signaling, and metabolism (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cordycepin may inhibit intracellular lipid accumulation through activation of AMPK via interaction with the γ1 subunit and might act as a novel AMPK activator for the treatment of hepatic steatosis, inflammation, liver injury, and a variety of tumors by activating the AMPK signaling pathway [ 12 , 16 , 17 ]. To determine whether cordycepin inhibits osteosarcoma cell growth through the AMPK pathway, we performed western blotting and found that the expression of p-AMPK was upregulated after treatment with cordycepin for 48 h. We also found that activation of AMPK was enhanced in the group treated with the combination of cordycepin and cisplatin compared to the group treated with cordycepin or cisplatin alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cordycepin has been comfirm to inhibit drug-resistance non-small cell lung cancer progression through activating AMPK signaling pathway [ 26 ]. Cordycepin might be a novel AMPK activator that binds the α1 and γ1 subunits near the autoinhibitory domain of AMPK [ 17 , 27 ]. Our study revealed that cordycepin mediated an increase in AMPK phosphorylation, thereby inhibiting the proliferation of osteosarcoma cells and that the expression of phosphorylated AMPK increased more significantly when cordycepin was used in combination with cisplatin than when it was administered alone.…”
Section: Discussionmentioning
confidence: 99%